Jurisprudential Analysis of Death Due to Electrocution - Akber, Elias Bin; Haque, Syed Md Tanjilul; Sultana, Sharmin; Barua, Ashim Kumar; Hossain, Zakir; Jahan, Israt (Central Medical College Journal, 2022)
Background: Minimum attention is given to electrocution deaths as we hardly come across these cases during autopsy. Electrocution has great impact on morbidity and mortality which can be prevented by public awareness and by adopting safety measures. Methods: An autopsy-based retrospective study of three years conducted by history of the cases, inquest report and by doing meticulous autopsy of each of the cases at Dhaka Medical College Mortuary. Results: We observed 139 electrocution deaths (1.03%) out of 13400 autopsies. Male victims i.e 123 (88.48%) outnumbered the females i.e in 16 cases (11.51%). The most affected age group was 21-30 years i.e 71 cases (51.07%) followed by 31-40 years in 38 cases (27.33%) and 41-50 years in 18 cases (12.94%). The most common places of electrocution were on the roadside i.e in 91 cases (65.46%) followed by the house in 48 cases (34.53%). High tension electric wires the commonest causative agent i.e in 78 cases (56.11%) followed by home appliances in 48 cases (34.53%) and water pump in 13 cases (9.35%). Regarding distribution of entry and corresponding exit wounds, we observed presence of both entry and exit wounds in 86 cases (61.87%) followed by no entry wounds in 29 cases (20.86%) and entry wounds in 24 cases (17.26%) Most of the entry wounds were present in the upper limbs i.e in 98 cases (70.50%) followed by head-neck in 16 cases (11.51%) and chest-abdomen in 15 cases (10.79%). Maximum exit wounds were observed in the lower limbs i.e in 106 cases (76.25%) followed by no exit wounds in 24 cases (17.26%). Considering manner of death, we observed all the 139 cases of electrocution i.e 100% were of accidental. Conclusion: Though cases of death due to electrocution are found in minimum numbers along with other unnatural deaths annually, they can be prevented by proper awareness and measures effectively. Central Medical College Journal Vol 5 No 1 Jan 2021 PP 13-19